The Perceived Effect of a Witness Security Program on Willingness to Testify - Demir, Mustafa (International criminal justice review, 2018)
To encourage witnesses to testify, witness security programs have been established to protect people who testify against offenders. Research on the impact of witness protection programs on the willingness of people to testify, however, is scarce. To fill the gap, this research was conducted in Turkey to investigate the perceived effect of a witness security program on witnesses’ willingness to testify while controlling for sociodemographic variables, including gender, marital status, age, employment, education level, economic status, and social status. The study used a self-administered survey of 732 individuals who were either a victim of a crime or a witness to a crime. The findings from the multivariate analysis showed that gender, social status, and employed had an impact on willingness to testify. Specifically, the findings showed that being male, having middle- or upper-class social status, and being unemployed increased the likelihood of willingness to testify. The other variables were not statistically significant predictors of willingness to testify. These findings suggest that a witness security program is an essential tool for increasing people’s willingness of testify and ensure an effective investigation, prosecution, and adjudication.